2018
DOI: 10.3847/1538-4357/aaa47c
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Observations of Heavily Obscured (Compton-thick) Active Galactic Nuclei Selected by the Swift/BAT Hard X-Ray Survey

Abstract: We present a uniform broadband X-ray (0.5-100.0 keV) spectral analysis of 12 Swift/Burst Alert Telescope (BAT) selected Compton-thick (log N H /cm −2 ≥ 24) Active Galactic Nuclei (CTAGNs) observed with Suzaku. The Suzaku data of 3 objects are published here for the first time. We fit the Suzaku and Swift spectra with models utilizing an analytic reflection code and those utilizing (Kawamuro et al. 2016a) suggests that the properties of these CTAGNs can be understood as a smooth extension from Compton-thin AGN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 101 publications
1
29
0
Order By: Relevance
“…These results are consistent with what is shown in Figure 11 by considering that most sources are at L 14−195 < 10 44 erg s −1 . The same trend is also reported from the X-ray studies of Compton-thick AGN Tanimoto et al 2016). They reported that secure Compton-thick AGN in the local universe do not preferentially locate within the AGN cut or wedge at L 14−195 < 10 43 erg s −1 .…”
Section: Luminosity Dependence Of Covering Factorsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with what is shown in Figure 11 by considering that most sources are at L 14−195 < 10 44 erg s −1 . The same trend is also reported from the X-ray studies of Compton-thick AGN Tanimoto et al 2016). They reported that secure Compton-thick AGN in the local universe do not preferentially locate within the AGN cut or wedge at L 14−195 < 10 43 erg s −1 .…”
Section: Luminosity Dependence Of Covering Factorsupporting
confidence: 82%
“…Follow-up studies below 10 keV have shown that the fraction of obscured (N H ≥ 10 22 cm −2 ) AGN highly depends on the intrinsic X-ray luminosities (e.g., Beckmann et al 2009;Burlon et al 2011;Ricci et al 2014;Kawamuro et al 2016a), and also proved to be an effective tool to identify previously missed class of AGN with small opening angle tori (e.g., Ueda et al 2007;Winter et al 2009;Eguchi et al 2009Eguchi et al , 2011Ricci et al 2011), and Compton-thick AGN Tanimoto et al 2016). Studies carried out by optical spectroscopy enable us to investigate the properties of extended (> 100 pc) narrow line regions (NLR; e.g., Hainline et al 2013Hainline et al , 2014a) through analysis of the [OIII]λ5007 emission line (Winter et al 2009;Ueda et al 2015) and also offer the opportunity to estimate the black hole masses through the broad line regions or velocity dispersion measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in slope between the one adopted in our paper (Γ ∼ 1.8) and Γ ∼1.5-1.6 can be responsible for our slightly higher value of column density given the degeneracy between the two parameters. We note, however, that once higher energy data are considered as in the work by Tanimoto et al (2018, including Swift/BAT), a photon index of ∼ 1.9 is found.…”
Section: Ngc1194 Spectral Fitsmentioning
confidence: 70%
“…More in detail, in these papers the reported column densities are 1.7 +0.24 −0.25 ×10 24 cm −2 , 0.81 +0.09 −0.08 ×10 24 cm −2 , 1.15 +0.37 −0.28 × 10 24 cm −2 , and 1.4 +0.3 −0.2 × 10 24 cm −2 , respectively. In all these works, the MYTorus model has been adopted (in M16 in its decoupled version), with the exception of Tanimoto et al (2018), where the N H reported above is referred to the phenomenological, best-fitting result. Although the derived column density value from our analysis lies in the upper envelope of the published results, we note that overall the Compton-thick nature of this source is widely confirmed; the line is strong and present in all datasets, and the derived value of EW is fully consistent with literature (e.g., EW=780 +160 −140 eV in M18).…”
Section: Ngc1194 Spectral Fitsmentioning
confidence: 99%
“…Adopting alternative values (i.e., Γ = 1.9, θ inc = 89 • , and θ op = 37 • ) instead of the default values, we can confirm that our conclusion is little affected. Specifically, our model is represented as torusabs*zpowerlw*zhighect +zpowerlw*zhighect *mtable{e-torus_20161121_2500M.fits} +atable{refl_fe_torus.fits} +[Best-fit Model of the XMM-Newton Spectra], almost the same as those used in past studies (e.g., Tanimoto et al 2018;Oda et al 2018). From the first to the third terms, we take account of the absorbed cutoff power law component from an AGN, the reflected emission, and the accompanying 6.4 keV iron-Kα line.…”
Section: Nustar Non-detection Due To Heavymentioning
confidence: 99%